A Mobile Science Index for Development - Canessa, E.; Zennaro, M. (International Journal of Interactive Mobile Technologies (iJIM), 2012)
A simple Mobile Science Potentiality Index (mSPI) is introduced as a barometer reflecting a new signal of world development through the capacity for a interconnected community to participate collectively in, and carry out, scientific studies using mobile devices. The mSP Index could be a new signal for world development.